Outbreak of NDM-5-Producing Proteus mirabilis During the COVID-19 Pandemic in an Argentine Hospital - Barbara Ghiglione; Ana Paula Rodriguez; María Sol Haim; Laura Esther Friedman; Nilton Lincopan; María Eugenia Ochiuzzi; José Alejandro Di Conza (Antibiotics)
Background: During the COVID-19 pandemic, the emergence of multidrug-resistant (MDR) pathogens, driven by heightened antibiotic usage and device-associated infections, has posed significant challenges to healthcare. This study reports an outbreak of Proteus mirabilis producing NDM-5 and CTX-M-15 β-lactamases in a hospital in Buenos Aires, Argentina, from October 2020 to April 2021. To our knowledge, this represents the first documented outbreak of NDM-5-producing P. mirabilis in the country. Methods: A total of 82 isolates were recovered from 40 patients, with 41.5% from blood cultures and 18.3% from respiratory and urinary samples, among others. Antimicrobial susceptibility testing, PCR-based methods, and MALDI-TOF MS cluster analysis were conducted. Whole genome sequencing (WGS) was performed to characterize the MLST, resistome and plasmid content. Biofilm formation assays and in vitro rifampicin susceptibility tests were also conducted. Result: Most isolates exhibited resistance to carbapenems, cephalosporins, aminoglycosides, and fluoroquinolones, while retaining susceptibility to aztreonam. Genetic analysis confirmed the co-presence of the blaNDM-5 and blaCTX-M-15 genes. Clonal relationships was supported by PCR-based typing and MALDI-TOF MS cluster analysis. WGS revealed a resistome comprising 25 resistance genes, including rmtB and both β-lactamases, as well as the presence of an incomplete IncQ1 replicon associated with multiple resistance determinants. MLST classified this clone as belonging to ST135. Despite the biofilm-forming capacity observed across strains, rifampicin demonstrated potential for disrupting established biofilms at concentrations ≥32 µg/mL in vitro. The MDR profile of the outbreak strain significantly limited therapeutic options. Conclusions: This study highlights the growing threat of NDM-producing P. mirabilis in Argentina. The absence of surveillance cultures from the index case limits insights into the outbreak’s origin. These findings underscore the importance of integrating genomic surveillance into infection control protocols to mitigate the spread of MDR pathogens.